Identifikasi Resiko Keselamatan Dan Kesehatan Kerja Pembangunan Gedung Bank Mandiri Kediri - Rekso Ajiono; Yosef Cahyo SP SP; April Gunarto; Sudjati Sudjati (Jurnal Teknika, 2020)
Every job must have risks and potential hazards that threaten, the existence of rules and regulations governing the implementation of work intended to minimize the occurrence of a work accident. The purpose of this study was to determine the types of work accidents, the causes of work accidents and the most dominant factors. This research method uses quantitative descriptive. The sample in this study amounted to 40 of 62 respondents. Data collection by distributing questionnaires to respondents. The results of research on the types of workplace accidents that occur are tripping, hammering, electric shock, in the hands and legs. While the causes of work accidents that occur are lack of knowledge of workers, physical conditions that do not support, do not wear personal protective equipment, the alarm system does not meet the requirements, the authority of the equipment due to frequent use. The most dominant factor of the types of work accidents is statement X1.3 (hammered) with a percentage value of 62.50%, and from the cause of work, an accident is statement Y1.3 (Not wearing personal protective equipment) with a percentage value of 65 %.